Entre racionalidad y espiritualidad en la tetralogía detectivesca de Rudolfo Anaya - Moukouti Onguédou, Georges (Acta Hispanica, 2014)
In this analysis we are faced with a subversion pattern of the detective novel. In fact, though the various plots are constructed – according to the classic detective story – for instance in a dynamic causal relationship, from now on we will have to count on a combination of events which are at the same time physical, mystical, magical, spiritual, and traditional on the vital path of the detective, as it is the case with the tetralogy of Rudolfo Anaya’s Zia Summer (1995), Rio Grande Fall (1996) Shaman Winter (1999) and Jemez Spring (2005). The action takes place in a Chicano area, where modernity and tradition, and above all, rationality and spirituality are mixed up.